Enjoying nutritious delicacies of sweet corn - Singh, Ritu (Indian Horticulture, 2019)
Inspite of availability of promising varieties, sweet corn is yet to assume popularity in our country. There is very little utilization of sweet corn in regular market. On the other hand, major portion of sweet corn is being utilized in hotels and big restaurants. Besides, there is lack of awareness on its nutritional value. Thus, there is an urgent need to develop entrepreneurship to harness the advantages associated with sweet corn. Since sweet corns need to be utilized immediately after harvesting, its cultivation should be encouraged in periurban agriculture. Market network must be developed to ensure household availability of sweet corn. This can only be attained with proper market leadership and policy support, which is presently lacking in India.